Comparative Analysis of The Structural-Semantic Aspects of The Concept "Work" In English and Uzbek Proverbs and Sayings (Texas Journal of Philology, Culture and History, 2024)
This article is devoted to the problems of concept in Modern English and Uzbek. It discusses the structural and semantic features of the concept “work” in compared languages